Ultrafine copper foil wire composite wire with diameter of 0.02-0.05 mm

By forming a fluorine-containing anti-corrosion layer and an outer protective layer on the outside of the copper foil core of the ultra-fine copper foil composite conductor, the deficiencies in corrosion resistance, mechanical strength and electromagnetic shielding performance of the conductor are solved, and higher mechanical strength is achieved , corrosion resistance and electromagnetic shielding effectiveness.

CN119340004AActive Publication Date: 2025-01-21DONGGUAN LINGKANG CABLE CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411541755.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-21
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing ultra-fine copper foil composite wires have shortcomings in corrosion resistance, mechanical strength and electromagnetic shielding performance, especially in high integrated circuit environments, signal transmission is susceptible to electromagnetic interference.

Method used

Using ultra-fine copper foil composite wires with a diameter of 0.02mm to 0.05mm, a fluorine-containing anti-corrosion layer and an outer protective layer are formed on the outside of the copper foil wire core, and fluorine-reinforced modified resin and composite polyethylene materials are used to optimize the molding structure and materials Composed to improve the mechanical strength, corrosion resistance and electromagnetic shielding effectiveness of the wire.

Benefits of technology

It significantly improves the mechanical strength and corrosion resistance of ultra -fine copper foil composite wires. At the same time, it enhances its electromagnetic shielding performance and insulation strength, and is suitable for signal transmission in the high -integrated circuit environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340004A_ABST
    Figure CN119340004A_ABST
Patent Text Reader

Abstract

The invention discloses an ultra-fine copper foil wire composite wire with the diameter of 0.02 mm to 0.05 mm, belongs to the technical field of composite wire processing, and is used for solving the technical problem that the corrosion resistance, the mechanical strength, the electromagnetic shielding performance and the insulating strength of an ultra-fine copper foil wire composite wire in the prior art need to be further improved. The anti-corrosion copper foil wire comprises a copper foil wire core, a fluorine-containing anti-corrosion layer and an outer protective layer, an insulating layer comprises the fluorine-containing anti-corrosion layer and the outer protective layer, and the fluorine-containing anti-corrosion layer is obtained after fluorine-reinforced modified resin is melted, coats the outer portion of the copper foil wire core and is cured. And through mutual cooperation of the fluorine anti-corrosion layer and the outer protection layer, the electromagnetic shielding effectiveness and the insulation strength of the composite wire are improved while the mechanical strength and the corrosion resistance of the composite wire are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite wire processing, and in particular to an ultra-fine copper foil composite wire with a diameter of 0.02 mm to 0.05 mm. Background Art

[0002] Ultra-fine copper foil wire conductor is a conductor material that uses ultra-fine copper foil wire as the conductive core. Through a specific composite process, the copper foil wire is composited with an insulating layer and a protective cover. The ultra-fine copper foil wire not only maintains the advantages of traditional copper foil wire, but also further improves the miniaturization and integration level of the conductor.

[0003] Prior art, a Chinese invention patent with publication number CN107170535A, discloses an ultra-fine skin-core wire conductor and its manufacturing equipment, including a skin layer and a core layer, the cross-section of the wire is circular, the cross-section of the core layer is circular, the cross-section of the skin layer is annular, the skin layer is wrapped around the outside of the core layer, the core layer is made of a conductive material composed of a mixture of carbon black particles and polyaniline, the skin layer is made of a high molecular polymer insulating material, and the outside of the skin layer is also provided with a wear-resistant groove, which is wound around the outside of the skin layer from top to bottom;

[0004] In the prior art, flexible electronic products such as flexible displays, flexible sensors, etc. require wires with extremely high flexibility and miniaturization levels. Ultrafine copper foil wire wires, with their good flexibility and miniaturization characteristics, have become ideal connecting wire materials for these products. However, traditional ultrafine copper foil wire composite wires use copper as the main material, which is easily corroded by the outside world and has low mechanical strength. During use, they are easily broken by external forces. At the same time, in a highly integrated circuit environment, signal transmission is easily affected by electromagnetic interference in the environment. Traditional composite wires usually sacrifice the insulation resistance of the external insulating layer to add conductive particles to the material to improve the electromagnetic shielding performance of the material, resulting in the insulation performance of the composite wire to be further improved.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide an ultra-fine copper foil composite wire with a diameter of 0.02mm to 0.05mm, which is used to solve the technical problems in the prior art that the ultra-fine copper foil composite wire has poor corrosion resistance and mechanical strength, and the electromagnetic shielding performance and insulation strength of the composite wire need to be further improved.

[0007] The object of the present invention can be achieved by the following technical scheme: an ultra-fine copper foil composite conductor with a diameter of 0.02mm to 0.05mm, comprising a copper foil core, a fluorine-containing anti-corrosion layer and an outer protective layer, wherein the insulating layer comprises a fluorine-containing anti-corrosion layer and an outer protective layer, wherein the fluorine-containing anti-corrosion layer is obtained by melting and coating a fluorine-reinforced modified resin on the outside of the copper foil core and then solidifying it, wherein the outer surface of the fluorine-containing anti-corrosion layer is provided with a plurality of grooves arranged parallel to the copper foil core, and the outer protective layer is obtained by melting and coating a composite polyethylene on the outside of the fluorine-containing anti-corrosion layer and then solidifying it;

[0008] The composite polyethylene consists of 100 parts of polyethylene mixture and 10-15 parts of epoxy resin by weight, wherein the polyethylene mixture consists of 100 parts of low-density polyethylene, 30-40 parts of modified polyethylene and 12-16 parts of modified graphite by weight.

[0009] Further, the fluorine-enhanced modified resin is processed by the following steps:

[0010] A1. Add butyl acrylate, perfluorooctyl acrylate, vinyl-terminated silicone oil, oleylamine and toluene into a nitrogen-protected reactor and stir. Raise the temperature of the reactor to 75-85°C. Add an initiator into the reactor and keep the temperature for 6-8h. Post-treat to obtain a fluorine-containing resin.

[0011] The synthetic reaction formula of fluorine-containing resin is:

[0012]

[0013] Where:

[0014] The synthetic reaction principle of fluorine-containing resin is:

[0015] Under the action of the initiator, the olefin double bonds on butyl acrylate, perfluorooctyl acrylate, terminal vinyl silicone oil and oleylamine molecules are used as active reaction sites to initiate a free radical polymerization reaction, thereby forming polyolefin segments cross-linked with polysiloxane segments, and the polyolefin segments are modified with fluorine-containing side chains, alkane side chains and octylamine side chains to prepare a fluorine-containing resin.

[0016] A2. Add fluorine-containing resin and epoxy resin into a reaction kettle and stir. Raise the temperature of the reaction kettle to 190-200°C and melt-mix for 30-50 minutes to obtain fluorine-reinforced modified resin.

[0017] Furthermore, in step A1, the amount ratio of butyl acrylate, perfluorooctyl acrylate, terminal vinyl silicone oil, oleylamine, toluene and initiator is 60-70g:15-18g:10-12g:17-19g:500mL:0.8-1.2g, the initiator is azobisisobutyronitrile, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to 80-90°C, and the solvent is evaporated under reduced pressure to obtain a fluorine-containing resin; in step A2, the weight ratio of the fluorine-containing resin to the epoxy resin is 7:2-3, and the epoxy resin is bisphenol A type epoxy resin E-51.

[0018] Further, the modified polyethylene is processed by the following steps:

[0019] B1. Mix low-density polyethylene powder, tea polyphenols, glycidyl methacrylate and initiator evenly and add them into an internal mixer at a temperature of 185-195°C, set the speed of the internal mixer to 50-60r / min, and mix for 10-15min to obtain a mixture;

[0020] B2. Transfer the mixture to a flat vulcanizer, increase the temperature of the flat vulcanizer to 190-200°C, increase the pressure to 9-10MPa, keep the temperature and pressure for 5-10 minutes, and obtain modified polyethylene after post-treatment.

[0021] The synthetic reaction mechanism of modified polyethylene is:

[0022] With tea polyphenols as antioxidant, low-density polyethylene powder, glycidyl methacrylate and initiator are evenly mixed, and the olefin double bonds on glycidyl methacrylate are used as active reaction sites. After vulcanization treatment, cross-linking bonding between glycidyl methacrylate and low-density polyethylene molecular chains is promoted, and a large number of epoxy groups are modified on the polyethylene molecular chains to prepare modified polyethylene.

[0023] Furthermore, in step B1, the weight ratio of the low-density polyethylene powder, tea polyphenols, glycidyl methacrylate and initiator is 100:1:5-7:0.5, and the initiator is benzoyl peroxide; in step B2, the post-treatment includes: after the vulcanization is completed, the material is cooled and discharged, crushed, the powder and xylene are added to the reactor in an amount of 1g:200mL and stirred, the temperature of the reactor is increased to reflux, the temperature is kept and stirred until the system is dissolved, the temperature of the reactor is lowered to room temperature, petroleum ether is added to the reactor, a large amount of solid is precipitated, suction is filtered, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain modified polyethylene.

[0024] Further, the modified graphite is processed by the following steps:

[0025] C1. Add flake graphite powder and modifier into a reactor, stir for 30-40 min at room temperature, and post-treat to obtain activated graphite powder;

[0026] C2. Place the activated graphite powder in a tubular furnace in a nitrogen atmosphere, raise the temperature of the tubular furnace to 300-350°C, keep the temperature for 10-20 minutes, cool and discharge the material to obtain expanded graphite;

[0027] C3, adding expanded graphite, pentacarbonyl iron and kerosene into a nitrogen-protected autoclave with closed stirring, raising the temperature of the autoclave to 260-280° C., heat preservation treatment for 90-120 min, and post-processing to obtain supported expanded graphite;

[0028] The synthetic reaction mechanism of supported expanded graphite is:

[0029] The flake graphite powder is mixed with a modifier and stirred at room temperature. The oxidizing substances in the modifier will attack the carbon atoms of the graphite to form carbon-oxygen bonds, increase the active sites on the graphite surface, change the surface properties of the graphite, and provide conditions for subsequent high-temperature expansion. The carbon atoms on the graphite surface are further oxidized by hydrogen peroxide to form more carbon-oxygen bonds and carboxyl functional groups to obtain activated graphite powder; at high temperatures, oxidation products such as water vapor and carbon dioxide between graphite layers escape quickly to generate huge internal pressure. At the same time, the carbon atoms between graphite layers are rearranged at high temperatures to form a looser structure, so that the graphite expands rapidly at high temperatures to form expanded graphite; at high temperatures, pentacarbonyl iron decomposes to produce iron atoms or iron nanoparticles and carbon monoxide, and the produced iron atoms or iron nanoparticles are adsorbed on the expanded graphite to form loaded expanded graphite.

[0030] C4. Add supported expanded graphite, modified nano-silica, ethyl orthosilicate and anhydrous ethanol into a reactor, disperse ultrasonically for 30-50 minutes and then stir. Raise the temperature of the reactor to 50-60°C, add a catalyst into the reactor, keep the reaction warm for 60-90 minutes, and obtain modified graphite by post-treatment.

[0031] The synthetic reaction mechanism of modified graphite is:

[0032] Under alkaline conditions, the siloxane bonds in the modified nano-silica and tetraethyl orthosilicate molecules are hydrolyzed to generate silanol groups, and the silanol groups are used as reactive sites to undergo condensation reactions with the reactive oxygen groups on the surface of the supported expanded graphite. A layer of nano-silica and polysiloxane coating is coated on the surface of the supported expanded graphite to prepare modified graphite.

[0033] Further, in step C1, the amount ratio of the flake graphite powder and the modifier is 1g:8-12mL, the modifier is obtained by mixing potassium permanganate and 80-90wt% sulfuric acid in an amount ratio of 1g:7mL, and the post-treatment includes: after the reaction is completed, suction filtration until no liquid drips, the filter cake and 20-30wt% hydrogen peroxide are added to the reactor in an amount ratio of 1g:8-10mL and stirred, the temperature of the reactor is increased to 75-85°C, stirred for 60-80min, the temperature of the reactor is lowered to room temperature, suction filtration, the filter cake is washed with purified water until neutral and then drained, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain activated graphite powder; in step C3, the amount ratio of the expanded graphite, pentacarbonyl iron, and kerosene is 7g:1g: 500mL, the post-treatment includes: after the reaction is completed, the pressure of the high-pressure reactor is reduced to room temperature, centrifuged, the solid is washed with acetone for 5 times and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain supported expanded graphite; in step C4, the amount ratio of the supported expanded graphite, modified nano-silicon dioxide, ethyl orthosilicate, anhydrous ethanol and catalyst is 10g:4g:3g:100mL:10mL, the catalyst is 0.3-0.5mol / L sodium hydroxide solution, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is reduced to room temperature, suction filtered, the filter cake is washed with purified water until neutral and then dried, the filter cake is placed in a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain modified graphite.

[0034] Further, the modified nano-silicon dioxide is processed by the following steps:

[0035] D1, adding nano-silicon dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane into a reactor and stirring, raising the temperature of the reactor to 50-60° C., adding a catalyst into the reactor, keeping the temperature for reaction for 50-60 minutes, and post-treating to obtain activated silicon dioxide powder;

[0036] D2. Add activated silica powder and toluene into a nitrogen-protected reactor and stir. Add isocyanatepropyltriethoxysilane into the reactor at room temperature and stir for 40-50 minutes. Post-treat to obtain modified nano-silica.

[0037] The synthetic reaction mechanism of modified silica is:

[0038] The surface of nano-silica is modified by coating with 3-aminopropyltriethoxysilane to prepare activated silica powder with a large number of amino groups on the surface; under the protection of nitrogen, the isocyanate group on the isocyanatepropyltriethoxysilane undergoes a condensation reaction with the amino group on the surface of the activated silica powder to prepare modified nano-silica with triethoxysilane-modified activated silica powder.

[0039] Furthermore, in step D1, the amount ratio of the nano-silica, anhydrous ethanol, 3-aminopropyltriethoxysilane and catalyst is 5g:30mL:1g:5mL, the catalyst is 0.3-0.5mol / L sodium hydroxide solution, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed with purified water until neutral and then dried, the filter cake is placed in a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain activated silica powder; in step D2, the amount ratio of the activated silica powder, toluene and isocyanatepropyltriethoxysilane is 5g:50mL:2g, and the post-treatment includes: after the reaction is completed, suction filtration is performed, the filter cake is washed with toluene 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain modified nano-silica.

[0040] Furthermore, the overall outer diameter of the wire is 0.02mm-0.05mm, for example, 0.02mm, 0.03mm, 0.04mm, 0.05mm, and has good flexibility, good bending resistance, good tensile strength, and good conductivity.

[0041] The present invention has the following beneficial effects:

[0042] 1. The ultra-fine copper foil composite conductor of the present invention selects fine copper foil as the conductor core, and sequentially forms a fluorine-containing anti-corrosion layer and an outer protective layer on the outside thereof by hot coating. By optimizing the molding structure of the fluorine-containing anti-corrosion layer and the material composition of the fluorine-containing anti-corrosion layer and the outer protective layer, the contact area between the fluorine-containing anti-corrosion layer and the outer protective layer is increased, and the fluorine-containing anti-corrosion layer and the outer protective layer are closely contacted, thereby improving the mechanical strength and corrosion resistance of the material. By optimizing the preparation method of the raw materials constituting the outer protective layer, the electromagnetic shielding effectiveness of the composite conductor is improved, and the insulation strength of the composite conductor material is increased.

[0043] 2. In the preparation process of the ultrafine copper foil composite wire of the present invention, perfluorooctyl acrylate is introduced into the fluorine-containing resin as a fluorine-containing monomer to improve the weather resistance, chemical corrosion resistance and thermal stability of the resin. At the same time, the addition of butyl acrylate and terminal vinyl silicone oil can improve the flexibility and processability of the resin and improve the tensile strength of the composite wire. By introducing bisphenol A epoxy resin, under high temperature environment, the epoxy resin undergoes ring-opening condensation with active groups such as amino groups and hydroxyl groups to form cross-linked bonds and hydroxyl groups at the same time, thereby enhancing the cross-linking density and intermolecular force of the resin, thereby further improving the tensile strength of the composite wire. In addition, the fluorine atom has high electronegativity and low polarizability, so that the fluorine-containing resin has excellent insulation properties, thereby improving the volume resistivity of the composite wire. The bisphenol A epoxy resin itself also has certain corrosion resistance and insulation properties, and it cooperates with the fluorine-containing resin to further improve its corrosion resistance and insulation strength.

[0044] 3. The ultra-fine copper foil composite conductor of the present invention uses modified graphite and modified polyethylene as reinforcing modifiers to enhance and modify low-density polyethylene. Under high temperature, the epoxy groups on the modified polyethylene molecules and the imino groups on the modified graphite molecules undergo ring-opening condensation to form a cross-linked reinforcement network in the low-density polyethylene material to obtain a polyethylene mixture. Both graphite and polysiloxane have good chemical stability. The formation of a multiphase structure of the composite polyethylene and the interaction of each component form a protective layer outside the fluorine-containing anti-corrosion layer, further improving the corrosion resistance of the composite conductor. Bisphenol A epoxy resin is used to enhance the polyethylene mixture to prepare a composite polyethylene. The siloxane bonds in the composite polyethylene molecules are catalyzed by high temperature and water vapor. Under the conditions of the agent, it is decomposed into highly reactive silanol groups, which react with active groups such as hydroxyl groups and imino groups on the surface of the fluorine-containing anti-corrosion layer or in the composite polyethylene molecules to form cross-linked bonds, thereby increasing the cross-linking degree of the material and further increasing the mechanical strength of the material. When preparing modified graphite, metal particles are loaded on the graphite to improve its electrical conductivity, and the loaded expanded graphite is coated and modified by nano-silica particles and polysiloxane. While providing insulation protection for the loaded expanded graphite, the modified graphite can be evenly dispersed in the modified polyethylene by utilizing its surface activity, thereby forming a conductive network in the outer protective layer, thereby effectively reflecting and absorbing electromagnetic waves, thereby improving the electromagnetic shielding performance of the material and ensuring the insulation performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0046] Figure 1 It is a schematic diagram of the three-dimensional structure of the ultra-fine copper foil composite conductor of the present invention;

[0047] Figure 2 It is a schematic diagram of the cross-sectional structure of the ultra-fine copper foil wire composite conductor in the present invention.

[0048] In the figure: 100, copper foil wire core; 200, fluorine-containing anti-corrosion layer; 300, outer protective layer. DETAILED DESCRIPTION

[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] In the present application, the vinyl-terminated silicone oil is selected from the divinyl-terminated polydimethylsiloxane of Green Union (Jining) Chemical Technology Co., Ltd., with a viscosity (25°C): 100±10MPa·S, and a vinyl content (molar ratio): 2.60±0.20%; the low-density polyethylene powder is selected from Dongguan Weicai Plastic Raw Materials Co., Ltd., with a brand of Sinopec Maoming and a density of 0.918g / cm 3 , melting point 122℃.

[0051] Example 1

[0052] This embodiment provides a method for preparing a fluorine-reinforced modified resin for an ultra-fine copper foil composite conductor, comprising the following steps:

[0053] A1. Preparation of fluorine-containing resin

[0054] Weigh: 600 g of butyl acrylate, 150 g of perfluorooctyl acrylate, 100 g of terminal vinyl silicone oil, 170 g of oleylamine and 5 L of toluene, add into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 75°C, add 8 g of azobisisobutyronitrile into the reactor, keep warm and react for 6 hours, after the reaction is completed, raise the temperature of the reactor to 80°C, evaporate the solvent under reduced pressure to obtain a fluorine-containing resin.

[0055] A2, Fluorine-reinforced modified resin

[0056] Fluorine-containing resin and bisphenol A epoxy resin E-51 were added into a reaction kettle at a weight ratio of 7:2 and stirred. The temperature of the reaction kettle was raised to 190° C. and melt-stirred for 30 minutes to obtain a fluorine-reinforced modified resin.

[0057] Example 2

[0058] This embodiment provides a method for preparing a fluorine-reinforced modified resin for an ultra-fine copper foil composite conductor, comprising the following steps:

[0059] A1. Preparation of fluorine-containing resin

[0060] Weigh: 650g of butyl acrylate, 165g of perfluorooctyl acrylate, 110g of terminal vinyl silicone oil, 180g of oleylamine and 5L of toluene, add into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 80°C, add 10g of azobisisobutyronitrile into the reactor, keep warm and react for 7h, after the reaction is completed, raise the temperature of the reactor to 85°C, evaporate the solvent under reduced pressure to obtain a fluorine-containing resin.

[0061] A2, Fluorine-reinforced modified resin

[0062] Fluorine-containing resin and bisphenol A epoxy resin E-51 were added into a reaction kettle at a weight ratio of 7:2.5 and stirred. The temperature of the reaction kettle was raised to 195° C. and melt-stirred for 40 minutes to obtain a fluorine-reinforced modified resin.

[0063] Example 3

[0064] This embodiment provides a method for preparing a fluorine-reinforced modified resin for an ultra-fine copper foil composite conductor, comprising the following steps:

[0065] A1. Preparation of fluorine-containing resin

[0066] Weigh: 700 g of butyl acrylate, 7180 g of perfluorooctyl acrylate, 120 g of terminal vinyl silicone oil, 190 g of oleylamine and 5 L of toluene, add into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 85°C, add 12 g of azobisisobutyronitrile into the reactor, keep warm and react for 8 hours, after the reaction is completed, raise the temperature of the reactor to 90°C, evaporate the solvent under reduced pressure to obtain a fluorine-containing resin.

[0067] A2, Fluorine-reinforced modified resin

[0068] Fluorine-containing resin and bisphenol A epoxy resin E-51 were added into a reaction kettle at a weight ratio of 7:3 and stirred. The temperature of the reaction kettle was increased to 200° C. and melt-stirred for 50 minutes to obtain a fluorine-reinforced modified resin.

[0069] Example 4

[0070] This embodiment provides a method for preparing composite polyethylene for ultra-fine copper foil composite conductor, comprising the following steps:

[0071] B1. Preparation of modified polyethylene

[0072] Low-density polyethylene powder, tea polyphenols, glycidyl methacrylate and benzoyl peroxide were uniformly added into an internal mixer at a temperature of 185° C. in a weight ratio of 100:1:5:0.5, the speed of the internal mixer was set to 50 r / min, and the internal mixer was mixed for 10 minutes to obtain a mixture;

[0073] The mixture was transferred to a flat-plate vulcanizer, the temperature of the flat-plate vulcanizer was increased to 190°C, the pressure was increased to 9MPa, and the treatment was carried out by heat and pressure maintenance for 5 minutes. The temperature was lowered, the material was discharged, and the material was crushed. The powder and xylene were added to the reactor in a concentration of 1g:200mL and stirred. The temperature of the reactor was increased to reflux, and the mixture was stirred until the system was dissolved. The temperature of the reactor was lowered to room temperature, and petroleum ether in an amount equal to the volume of xylene was added to the reactor. A large amount of solid precipitated, which was filtered, and the filter cake was transferred to a drying oven at a temperature of 60°C and dried to constant weight to obtain modified polyethylene.

[0074] B2. Preparation of expanded graphite

[0075] Potassium permanganate and 80 wt % sulfuric acid were mixed uniformly at a ratio of 1 g:7 mL to obtain a modifier;

[0076] Add flake graphite powder and modifier into a reactor at a ratio of 1 g: 8 mL, stir at room temperature for 30 min, filter until no liquid drips after the reaction is completed, add filter cake and 20 wt% hydrogen peroxide into the reactor at a ratio of 1 g: 8 mL, stir, raise the temperature of the reactor to 75° C., stir for 60 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 70° C., and vacuum dry to constant weight to obtain activated graphite powder;

[0077] The activated graphite powder was placed in a tubular furnace in a nitrogen atmosphere, the temperature of the tubular furnace was raised to 300°C, the temperature was kept for 10 minutes, the temperature was lowered and the material was discharged to obtain expanded graphite.

[0078] B3. Preparation of supported expanded graphite

[0079] Weigh: 70 g of expanded graphite, 10 g of iron pentacarbonyl, and 5 L of kerosene are added to a nitrogen-protected autoclave and stirred in a closed manner. The temperature of the autoclave is raised to 260° C. During the heating process, the pressure of the autoclave is controlled to be lower than 0.2 MPa by a pressure relief valve. The autoclave is kept warm for 90 minutes. After the reaction is completed, the pressure of the autoclave is reduced to room temperature and centrifuged. The solid is washed with acetone 5 times and then dried. The filter cake is transferred to a drying oven at a temperature of 60° C. and vacuum dried to constant weight to obtain supported expanded graphite.

[0080] B4. Preparation of modified nano-silica

[0081] Weigh: 50 g of nano-silica, 300 mL of anhydrous ethanol and 10 g of 3-aminopropyltriethoxysilane, add them into a reactor and stir, raise the temperature of the reactor to 50°C, add 50 mL of 0.3 mol / L sodium hydroxide solution into the reactor, and keep the reaction for 50 minutes. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, place the filter cake in a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain activated silica powder;

[0082] Weigh: 50 g of activated silica powder and 500 mL of toluene are added to a nitrogen-protected reactor and stirred. At room temperature, 20 g of isocyanatepropyltriethoxysilane is added to the reactor and stirred for 40 minutes. After the reaction is completed, filter and wash the filter cake with toluene three times and then dry it. Transfer the filter cake to a drying oven at 70°C and vacuum dry it to constant weight to obtain modified nano-silica.

[0083] B5. Preparation of modified graphite

[0084] Weigh: 100 g of supported expanded graphite, 40 g of modified nano-silica, 30 g of ethyl orthosilicate, and 1000 mL of anhydrous ethanol, add them into a reactor, stir after ultrasonic dispersion for 30 minutes, raise the temperature of the reactor to 50°C, add 10 mL of 0.3 mol / L sodium hydroxide solution into the reactor, and keep the reaction for 60 minutes. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, place the filter cake in a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain modified graphite.

[0085] B6. Preparation of composite polyethylene

[0086] Weigh out by weight: 100 parts of low-density polyethylene, 30 parts of modified polyethylene and 12 parts of modified graphite, add them into a twin-screw extruder, the temperatures of the 6 temperature sections from the feed end to the discharge end of the twin-screw extruder are 190° C., 195° C., 195° C., 195° C., 200° C., the main shaft speed of the twin-screw extruder is 15 r / min, and the mixture is crushed after melt extrusion to obtain a polyethylene mixture;

[0087] Weigh 100 parts of polyethylene mixture and 10 parts of bisphenol A epoxy resin E-51 by weight, add them into a reaction kettle and stir, increase the temperature of the reaction kettle to 190° C., melt and stir for 30 minutes, and obtain composite polyethylene.

[0088] Example 5

[0089] This embodiment provides a method for preparing composite polyethylene for ultra-fine copper foil composite conductor, comprising the following steps:

[0090] B1. Preparation of modified polyethylene

[0091] Low-density polyethylene powder, tea polyphenols, glycidyl methacrylate and benzoyl peroxide were uniformly added into an internal mixer at a temperature of 190° C. in a weight ratio of 100:1:6:0.5, the speed of the internal mixer was set to 55 r / min, and the internal mixer was kneaded for 13 minutes to obtain a mixture;

[0092] The mixture was transferred to a flat-plate vulcanizer, the temperature of the flat-plate vulcanizer was increased to 195°C, the pressure was increased to 9.5MPa, and the treatment was carried out by heat and pressure maintenance for 8 minutes. The temperature was lowered, the material was discharged, and the material was crushed. The powder and xylene were added to the reactor in a concentration of 1g:200mL and stirred. The temperature of the reactor was increased to reflux, and the mixture was stirred until the system was dissolved. The temperature of the reactor was lowered to room temperature, and petroleum ether in an amount equal to the volume of xylene was added to the reactor. A large amount of solid precipitated, which was filtered off and the filter cake was transferred to a drying oven at a temperature of 65°C and dried to constant weight to obtain modified polyethylene.

[0093] B2. Preparation of expanded graphite

[0094] Potassium permanganate and 80-90 wt % sulfuric acid are mixed uniformly at a ratio of 1 g:7 mL to obtain a modifier;

[0095] Add flake graphite powder and modifier into a reactor at a ratio of 1 g:10 mL, stir at room temperature for 35 min, filter until no liquid drips after the reaction is completed, add filter cake and 25 wt% hydrogen peroxide into the reactor at a ratio of 1 g:9 mL and stir, raise the temperature of the reactor to 80°C, stir for 70 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until neutral and then drain, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry to constant weight to obtain activated graphite powder;

[0096] The activated graphite powder was placed in a tubular furnace in a nitrogen atmosphere, the temperature of the tubular furnace was raised to 330°C, the temperature was kept for 15 minutes, the temperature was lowered and the material was discharged to obtain expanded graphite.

[0097] B3. Preparation of supported expanded graphite

[0098] Weigh: 70 g of expanded graphite, 10 g of iron pentacarbonyl, and 5 L of kerosene are added to a nitrogen-protected autoclave and stirred in a closed manner. The temperature of the autoclave is raised to 270° C. During the heating process, the pressure of the autoclave is controlled to be lower than 0.2 MPa by a pressure relief valve, and the heat treatment is carried out for 105 min. After the reaction is completed, the pressure of the autoclave is reduced to room temperature, centrifuged, the solid is washed with acetone 5 times and then dried, and the filter cake is transferred to a drying oven at a temperature of 65° C. and vacuum dried to constant weight to obtain supported expanded graphite.

[0099] B4. Preparation of modified nano-silica

[0100] Weigh: 50 g of nano-silica, 300 mL of anhydrous ethanol and 10 g of 3-aminopropyltriethoxysilane, add them into a reactor and stir, raise the temperature of the reactor to 50-60°C, add 50 mL of 0.4 mol / L sodium hydroxide solution into the reactor, and keep the reaction for 55 minutes. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, place the filter cake in a drying oven at a temperature of 75°C, and vacuum dry it to constant weight to obtain activated silica powder;

[0101] Weigh: 50 g of activated silica powder and 500 mL of toluene are added to a nitrogen-protected reactor and stirred. At room temperature, 20 g of isocyanatepropyltriethoxysilane is added to the reactor and stirred for 45 minutes. After the reaction is completed, filter and wash the filter cake with toluene three times and then dry it. Transfer the filter cake to a drying oven at 75°C and vacuum dry it to constant weight to obtain modified nano-silica.

[0102] B5. Preparation of modified graphite

[0103] Weigh: 100g of supported expanded graphite, 40g of modified nano-silica, 30g of ethyl orthosilicate, and 1000mL of anhydrous ethanol, add them into a reactor, stir after ultrasonic dispersion for 30-50min, raise the temperature of the reactor to 50-60°C, add 10mL of 0.4mol / L sodium hydroxide solution into the reactor, keep warm for 75min, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, place the filter cake in a drying oven at a temperature of 75°C, and vacuum dry it to constant weight to obtain modified graphite.

[0104] B6. Preparation of composite polyethylene

[0105] Weigh out by weight: 100 parts of low-density polyethylene, 35 parts of modified polyethylene and 14 parts of modified graphite, add them into a twin-screw extruder, the temperatures of the 6 temperature sections from the feed end to the discharge end of the twin-screw extruder are 190° C., 195° C., 195° C., 195° C., 195° C., 200° C., the main shaft speed of the twin-screw extruder is 15 r / min, and the mixture is crushed after melt extrusion to obtain a polyethylene mixture;

[0106] Weigh 100 parts of polyethylene mixture and 13 parts of bisphenol A epoxy resin E-51 by weight, add them into a reaction kettle and stir, increase the temperature of the reaction kettle to 195° C., melt-mix for 40 minutes, and obtain composite polyethylene.

[0107] Example 6

[0108] This embodiment provides a method for preparing composite polyethylene for ultra-fine copper foil composite conductor, comprising the following steps:

[0109] B1. Preparation of modified polyethylene

[0110] Low-density polyethylene powder, tea polyphenols, glycidyl methacrylate and benzoyl peroxide were uniformly added into an internal mixer at a temperature of 195° C. in a weight ratio of 100:1:7:0.5, the speed of the internal mixer was set to 60 r / min, and the internal mixer was kneaded for 15 minutes to obtain a mixture;

[0111] The mixture was transferred to a flat-plate vulcanizer, the temperature of the flat-plate vulcanizer was increased to 200°C, the pressure was increased to 10MPa, and the heat and pressure were maintained for 10 minutes. The temperature was lowered, the material was discharged, and it was crushed. The powder and xylene were added to the reactor in a concentration of 1g:200mL and stirred. The temperature of the reactor was increased to reflux, and the mixture was stirred until the system was dissolved. The temperature of the reactor was lowered to room temperature, and petroleum ether in an amount equal to the volume of xylene was added to the reactor. A large amount of solid precipitated, which was filtered, and the filter cake was transferred to a drying oven at a temperature of 70°C and dried to constant weight to obtain modified polyethylene.

[0112] B2. Preparation of expanded graphite

[0113] Potassium permanganate and 90 wt % sulfuric acid were mixed uniformly at a ratio of 1 g:7 mL to obtain a modifier;

[0114] Add flake graphite powder and modifier into a reactor at a ratio of 1 g:12 mL, stir at room temperature for 40 min, filter until no liquid drips after the reaction is completed, add filter cake and 30 wt% hydrogen peroxide into the reactor at a ratio of 1 g:10 mL, stir, raise the temperature of the reactor to 85° C., stir for 80 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 80° C., and vacuum dry to constant weight to obtain activated graphite powder;

[0115] The activated graphite powder was placed in a tubular furnace in a nitrogen atmosphere, the temperature of the tubular furnace was raised to 350°C, and the temperature was kept for 20 minutes, and the material was cooled and discharged to obtain expanded graphite.

[0116] B3. Preparation of supported expanded graphite

[0117] Weigh: 70g of expanded graphite, 10g of pentacarbonyl iron, and 5L of kerosene are added to a nitrogen-protected autoclave and stirred in a closed manner. The temperature of the autoclave is raised to 280°C. During the heating process, the pressure of the autoclave is controlled to be lower than 0.2MPa by a pressure relief valve. The autoclave is kept warm for 120min. After the reaction is completed, the pressure of the autoclave is reduced to room temperature and centrifuged. The solid is washed with acetone 5 times and then dried. The filter cake is transferred to a drying oven at a temperature of 70°C and vacuum dried to constant weight to obtain supported expanded graphite.

[0118] B4. Preparation of modified nano-silica

[0119] Weigh: 50 g of nano-silica, 300 mL of anhydrous ethanol and 10 g of 3-aminopropyltriethoxysilane, add them into a reactor and stir, raise the temperature of the reactor to 60°C, add 50 mL of 0.5 mol / L sodium hydroxide solution into the reactor, and keep the temperature for 60 minutes. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, place the filter cake in a drying oven at 80°C, and vacuum dry it to constant weight to obtain activated silica powder;

[0120] Weigh: 50 g of activated silica powder and 500 mL of toluene are added to a nitrogen-protected reactor and stirred. At room temperature, 20 g of isocyanatepropyltriethoxysilane is added to the reactor and stirred for 50 minutes. After the reaction is completed, filter and wash the filter cake with toluene three times and then dry it. Transfer the filter cake to a drying oven at 80°C and vacuum dry it to constant weight to obtain modified nano-silica.

[0121] B5. Preparation of modified graphite

[0122] Weigh: 100 g of supported expanded graphite, 40 g of modified nano-silica, 30 g of ethyl orthosilicate, and 1000 mL of anhydrous ethanol, add them to a reactor, stir after ultrasonic dispersion for 50 minutes, raise the temperature of the reactor to 60°C, add 10 mL of 0.5 mol / L sodium hydroxide solution to the reactor, and keep the reaction for 90 minutes. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, place the filter cake in a drying oven at a temperature of 80°C, and vacuum dry it to constant weight to obtain modified graphite.

[0123] B6. Preparation of composite polyethylene

[0124] Weigh out by weight: 100 parts of low-density polyethylene, 40 parts of modified polyethylene and 16 parts of modified graphite, add them into a twin-screw extruder, the temperatures of the 6 temperature sections from the feed end to the discharge end of the twin-screw extruder are 190° C., 195° C., 195° C., 195° C., 195° C., 200° C., the main shaft speed of the twin-screw extruder is 15 r / min, and the mixture is crushed after melt extrusion to obtain a polyethylene mixture;

[0125] Weigh 100 parts of polyethylene mixture and 15 parts of bisphenol A epoxy resin E-51 by weight, add them into a reaction kettle and stir, increase the temperature of the reaction kettle to 200° C., melt-mix for 50 minutes, and obtain composite polyethylene.

[0126] Example 7

[0127] Please refer to the attached Figure 1-2 This embodiment provides a method for preparing an ultra-fine copper foil composite conductor, comprising the following steps:

[0128] S1. Add the fluorine-enhanced modified resin prepared in Example 1 into a melting furnace at a temperature of 190° C., heat the fluorine-enhanced modified resin until it melts, and obtain a fluid fluorine-enhanced modified resin coating liquid;

[0129] S2, adding the composite polyethylene prepared in Example 4 into a melting furnace at a temperature of 190° C., and heating the composite polyethylene until the composite polyethylene is melted to obtain a fluid composite polyethylene coating liquid;

[0130] S3, select a copper foil wire with a diameter of 0.02 mm as the copper foil wire core 100, heat it to 500°C, keep it warm for 2 minutes, pass it through a melting furnace filled with a fluorine-enhanced modified resin coating liquid, and then pass it through a forming hole, and water-cool it to solidify it, forming a fluorine-containing anti-corrosion layer 200 with a thickness of 0.008 mm on the surface of the copper foil wire core 100, and the fluorine-containing anti-corrosion layer 200 is provided with a plurality of grooves arranged parallel to the copper foil wire core 100, to obtain a composite conductor blank;

[0131] S4. The composite conductor blank passes through a melting furnace filled with composite polyethylene coating liquid without being dried, and then passes through a forming hole, where it is cooled and solidified, and an outer protective layer 300 with a thickness of 0.015 mm is formed on the surface of the composite conductor blank to obtain a composite conductor with an insulating layer covering the wire core.

[0132] Example 8

[0133] Please refer to the attached Figure 1-2 This embodiment provides a method for preparing an ultra-fine copper foil composite conductor, comprising the following steps:

[0134] S1. Add the fluorine-enhanced modified resin prepared in Example 2 into a melting furnace at a temperature of 195° C., heat the fluorine-enhanced modified resin until it melts, and obtain a fluid fluorine-enhanced modified resin coating liquid;

[0135] S2, adding the composite polyethylene prepared in Example 5 into a melting furnace at a temperature of 195° C., and heating the composite polyethylene until the composite polyethylene is melted to obtain a fluid composite polyethylene coating liquid;

[0136] S3, select a copper foil wire with a diameter of 0.03 mm as the copper foil wire core 100, heat it to 600°C, keep it warm for 2.5 minutes, pass it through a melting furnace filled with a fluorine-enhanced modified resin coating liquid, and then pass it through a forming hole, and water-cool it to solidify it, forming a fluorine-containing anti-corrosion layer 200 with a thickness of 0.010 mm on the surface of the copper foil wire core 100, and the fluorine-containing anti-corrosion layer 200 is provided with a plurality of grooves arranged parallel to the copper foil wire core 100, to obtain a composite conductor blank;

[0137] S4. The composite conductor blank passes through a melting furnace filled with composite polyethylene coating liquid without being dried, and then passes through a forming hole, where it is cooled and solidified, and an outer protective layer 300 with a thickness of 0.017 mm is formed on the surface of the composite conductor blank to obtain a composite conductor with an insulating layer covering the wire core.

[0138] Example 9

[0139] Please refer to the attached Figure 1-2 This embodiment provides a method for preparing an ultra-fine copper foil composite conductor, comprising the following steps:

[0140] S1, adding the fluorine-enhanced modified resin prepared in Example 3 into a melting furnace at a temperature of 200° C., and heating the fluorine-enhanced modified resin until the fluorine-enhanced modified resin is melted to obtain a fluid fluorine-enhanced modified resin coating liquid;

[0141] S2, adding the composite polyethylene prepared in Example 6 into a melting furnace at a temperature of 200° C., and heating the composite polyethylene until the composite polyethylene is melted to obtain a fluid composite polyethylene coating liquid;

[0142] S3, select a copper foil wire with a diameter of 0.05 mm as the copper foil wire core 100, heat it to 700°C, keep it warm for 3 minutes, pass it through a melting furnace filled with a fluorine-enhanced modified resin coating liquid, and then pass it through a forming hole, and water-cool it to solidify it, forming a fluorine-containing anti-corrosion layer 200 with a thickness of 0.012 mm on the surface of the copper foil wire core 100, and the fluorine-containing anti-corrosion layer 200 is provided with a plurality of grooves arranged parallel to the copper foil wire core 100, to obtain a composite conductor blank;

[0143] S4. The composite conductor blank passes through a melting furnace filled with composite polyethylene coating liquid without being dried, and then passes through a forming hole, where it is cooled and solidified, and an outer protective layer 300 with a thickness of 0.018 mm is formed on the surface of the composite conductor blank to obtain a composite conductor with an insulating layer covering the wire core.

[0144] Comparative Example 1

[0145] The difference between this comparative example and Example 9 is that, in Example 3, when preparing the fluorine-reinforced resin, no bisphenol A epoxy resin is added in step A2.

[0146] Comparative Example 2

[0147] The difference between this comparative example and Example 9 is that when preparing the composite polyethylene in Example 6, no modified polyethylene is added when preparing the polyethylene mixture in step B6.

[0148] Comparative Example 3

[0149] The difference between this comparative example and Example 9 is that, when preparing the composite polyethylene in Example 6, step B5 is eliminated, and the modified graphite in step B6 is replaced by the supported expanded graphite in step B3.

[0150] Comparative Example 4

[0151] The difference between this comparative example and Example 9 is that, when preparing the composite polyethylene in Example 6, step B3 is eliminated, and the supported expanded graphite in step B6 is replaced by the expanded graphite in step B2.

[0152] Performance Test:

[0153] The tensile strength, elongation at break, maximum bending degree, and volume resistivity at 20° C. of the composite wires prepared in Examples 7-9 and Comparative Examples 1-4 were measured with reference to the standard GB / T 11016.2-2009 "Plastic insulated and rubber insulated telephone cords Part 2: Polyvinyl chloride insulated telephone cords";

[0154] The shielding effectiveness of the composite wires prepared in Examples 7-9 and Comparative Examples 1-4 was measured with reference to the standard GB / T 30842-2014 “Requirements and Measurement Methods for Electromagnetic Shielding Effectiveness in High Voltage Test Laboratories”. The specific test results are shown in Table 1 below.

[0155] Table 1-Performance test data of the sample

[0156]

[0157] Data Analysis:

[0158] Comparing and analyzing the data in the above table, the tensile strength of the composite wire prepared by the present invention is 32.5MPa, the elongation at break is 375%, the maximum curvature is 15mm, the shielding effectiveness is 37.2dB, and the volume resistivity is 1.71×10 17 Ω·m, and all performance data are better than those of the comparative example, which fully illustrates that the present application optimizes the material composition of the fluorine-containing anti-corrosion layer and the outer protective layer, and cooperates with the fluorine anti-corrosion layer and the outer protective layer to improve the mechanical strength and corrosion resistance of the composite conductor while also improving the electromagnetic shielding effectiveness and insulation strength of the composite conductor.

[0159] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An ultra-fine copper foil composite conductor with a diameter of 0.02 mm to 0.05 mm, comprising a copper foil core (100) and an insulating layer covering the outside of the copper foil core (100), characterized in that: The insulating layer comprises a fluorine-containing anti-corrosion layer (200) and an outer protective layer (300), wherein the fluorine-containing anti-corrosion layer (200) is obtained by melting and coating a fluorine-reinforced modified resin on the outside of a copper foil wire core (100) and then solidifying it, the outer surface of the fluorine-containing anti-corrosion layer (200) is provided with a plurality of grooves arranged parallel to the copper foil wire core (100), and the outer protective layer (300) is obtained by melting and coating a composite polyethylene on the outside of the fluorine-containing anti-corrosion layer (200) and then solidifying it; The composite polyethylene consists of 100 parts of polyethylene mixture and 10-15 parts of epoxy resin by weight, wherein the polyethylene mixture consists of 100 parts of low-density polyethylene, 30-40 parts of modified polyethylene and 12-16 parts of modified graphite by weight.

2. The ultra-fine copper foil composite wire with a diameter of 0.02 mm to 0.05 mm according to claim 1, characterized in that: Fluorine-enhanced modified resin is processed by the following steps: A1. Add butyl acrylate, perfluorooctyl acrylate, vinyl-terminated silicone oil, oleylamine and toluene into a nitrogen-protected reactor and stir. Raise the temperature of the reactor to 75-85°C. Add an initiator into the reactor and keep the temperature for 6-8h. Post-treat to obtain a fluorine-containing resin. A2. Add fluorine-containing resin and epoxy resin into a reaction kettle and stir. The temperature of the reaction kettle is increased to 190-200°C. Melt and stir for 30-50 minutes to obtain fluorine-reinforced modified resin.

3. The ultra-fine copper foil composite wire with a diameter of 0.02 mm to 0.05 mm according to claim 2, characterized in that: In step A1, the amount ratio of butyl acrylate, perfluorooctyl acrylate, terminal vinyl silicone oil, oleylamine, toluene and initiator is 60-70g:15-18g:10-12g17-19g:500mL:0.8-1.2g, and the initiator is azobisisobutyronitrile; in step A2, the weight ratio of the fluorine-containing resin and the epoxy resin is 7:2-3, and the epoxy resin is bisphenol A type epoxy resin E-51.

4. The ultra-fine copper foil composite wire with a diameter of 0.02 mm to 0.05 mm according to claim 1, characterized in that: Modified polyethylene is obtained by the following steps: B1. Mix low-density polyethylene powder, tea polyphenols, glycidyl methacrylate and initiator evenly and add them into an internal mixer at a temperature of 185-195°C, set the speed of the internal mixer to 50-60r / min, and mix for 10-15min to obtain a mixture; B2. Transfer the mixture to a flat vulcanizer, increase the temperature of the flat vulcanizer to 190-200°C, increase the pressure to 9-10MPa, keep the temperature and pressure for 5-10 minutes, and obtain modified polyethylene after post-treatment.

5. The ultra-fine copper foil composite wire with a diameter of 0.02 mm to 0.05 mm according to claim 4, characterized in that: In step B1, the weight ratio of the low-density polyethylene powder, tea polyphenols, glycidyl methacrylate and initiator is 100:1:5-7:0.5, and the initiator is benzoyl peroxide.

6. The ultra-fine copper foil composite wire with a diameter of 0.02 mm to 0.05 mm according to claim 1, characterized in that: Modified graphite is processed by the following steps: C1. Add flake graphite powder and modifier into a reactor, stir for 30-40 min at room temperature, and post-treat to obtain activated graphite powder; C2. Place the activated graphite powder in a tubular furnace in a nitrogen atmosphere, raise the temperature of the tubular furnace to 300-350°C, keep the temperature for 10-20 minutes, cool and discharge the material to obtain expanded graphite; C3, adding expanded graphite, pentacarbonyl iron and kerosene into a nitrogen-protected autoclave with closed stirring, raising the temperature of the autoclave to 260-280° C., heat preservation treatment for 90-120 min, and post-processing to obtain supported expanded graphite; C4. Add supported expanded graphite, modified nano-silica, ethyl orthosilicate and anhydrous ethanol into a reactor, disperse ultrasonically for 30-50 minutes and then stir. Raise the temperature of the reactor to 50-60°C, add a catalyst into the reactor, keep the reaction warm for 60-90 minutes, and obtain modified graphite by post-treatment.

7. The ultra-fine copper foil composite wire with a diameter of 0.02 mm to 0.05 mm according to claim 6, characterized in that: In step C1, the amount ratio of the flake graphite powder to the modifier is 1g:8-12mL, and the modifier is obtained by uniformly mixing potassium permanganate and 80-90wt% sulfuric acid in an amount ratio of 1g:7mL; in step C3, the amount ratio of the expanded graphite, pentacarbonyl iron, and kerosene is 7g:1g:500mL; in step C4, the amount ratio of the supported expanded graphite, modified nano-silicon dioxide, tetraethyl orthosilicate, anhydrous ethanol, and the catalyst is 10g:4g:3g:100mL:10mL, and the catalyst is 0.3-0.5mol / L sodium hydroxide solution.

8. The ultra-fine copper foil composite wire with a diameter of 0.02 mm to 0.05 mm according to claim 6, characterized in that: Modified nano-silica is processed by the following steps: D1, adding nano-silicon dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane into a reactor and stirring, raising the temperature of the reactor to 50-60° C., adding a catalyst into the reactor, keeping the temperature for reaction for 50-60 minutes, and post-treating to obtain activated silicon dioxide powder; D2. Add activated silica powder and toluene into a nitrogen-protected reactor and stir. Add isocyanatepropyltriethoxysilane into the reactor at room temperature and stir for 40-50 minutes. Post-treat to obtain modified nano-silica.

9. The ultra-fine copper foil composite wire with a diameter of 0.02 mm to 0.05 mm according to claim 8, characterized in that: In step D1, the amount ratio of the nano-silica, anhydrous ethanol, 3-aminopropyltriethoxysilane and the catalyst is 5g:30mL:1g:5mL, and the catalyst is 0.3-0.5mol / L sodium hydroxide solution; in step D2, the amount ratio of the activated silica powder, toluene and isocyanatepropyltriethoxysilane is 5g:50mL:2g.

10. The ultra-fine copper foil composite wire with a diameter of 0.02 mm to 0.05 mm according to claim 1, characterized in that: The overall outer diameter of the wire is 0.02mm--0.05mm.

Citation Information

Patent Citations

  • Super-fine sheath-core wire and preparation equipment therefor

    CN107170535A

  • High temperature resisting improved isotatic polypropylene capacitor metallized film and preparation method thereof

    CN103937101A

  • Preparation method of hydrophobic and oleophobic paper packaging material

    CN106592333A

  • High-strength anti-aging insulated wire for wind power and preparation method of high-strength anti-aging insulated wire

    CN118155914A

  • Electrical heating cable or electric heat belt with insulating sleeve in layer structure

    CN1770931A